Effect of the metal ion-induced carbonylation modification of mitochondrial membrane channel protein VDAC on cell vitality, seedling growth and seed aging - Li, Ying; Liu, Chang; Qi, Manyao; Ye, Tiantian; Kang, Ying; Wang, Yu; Wang, Xiaofeng; Xue, Hua (Frontiers in Plant Science, 2023)
Seeds are the most important carrier of germplasm preservation. However, an irreversible decrease in vigor can occur after the maturation of seeds, denoted as seed aging. Mitochondrion is a crucial organelle in initiation programmed cell death during seed aging. However, the underlying mechanism remains unclear. Our previous proteome study found that 13 mitochondria proteins underwent carbonylation modification during the aging of Ulmus pumila L. (Up) seeds. In this study, twelve of these proteins were identified as Fe2+/Cu2+/Zn2+ binding proteins detected by immobilized metal affinity chromatography (IMAC), including mitochondrial voltage-dependent anion channel (VDAC). This suggests that metal-binding proteins in mitochondria are the main targets of carbonylation during seed aging. In IMAC assay, UpVDAC showed binding abilities to all the three metal ions. His204Ala (H204A) and H219A mutated UpVDAC proteins lost their metal binding ability, and became insensitive to metal-catalyzed oxidation (MCO) induced carbonylation. The overexpression of wild-type UpVDAC made yeast cells more sensitive to oxidative stress, retarded the growth of Arabidopsis seedlings and accelerated the seed aging, while overexpression of mutated UpVDAC weakened these effects of VDAC. These results reveal the relationship between the metal binding ability and carbonylation modification, as well as the probable function of VDAC in regulating cell vitality, seedling growth and seed aging.